Preliminary investigation of combined laser and microwave treatment for stone biodeterioration. (August 2015) - Mascalchi, Marta; Osticioli, Iacopo; Riminesi, Cristiano; Cuzman, Oana Adriana; Salvadori, Barbara; Siano, Salvatore
<x content-type="archive" xml:space="preserve">Abstract</x> In this work, the potential applications of surface laser removal of biological crusts from Carrara marble artefacts and in-depth microwave selective heating for treatment of possible endolithic growths have been evaluated. The investigations were carried out on seriously deteriorated marble fragments from the monumental tombs of the English Cemetery in Florence, Italy. The second harmonic (532 nm) of a Q-switched Nd:YAG laser was used for cleaning while a microwave system emitting at 2.45 GHz was tested for in-depth sterilization. As is well known, microwaves are strongly absorbed by water via dipolar energy dissipation, which permits selective heating of endolithic organisms. The effects of laser and microwave treatments were characterized using scanning electron microscopy (SEM) along with chlorophyll fluorescence with pulsed amplitude modulated imaging. The latter has allowed the quantification of the impairment effects to photosystem II of epilithic phototrophic organism residues by mapping the maximum quantum yield, while the damage to endolithic growths was evaluated by means of SEM following osmium tetroxide staining of cytoplasmic lipids. The results provide an early picture of the development and application perspectives of the combined laser and microwave treatments in the conservation of biodeteriorated stone artefacts.